Relationship between Educational Attainment and Living Standard of the Poor and Vulnerable Households in Nigeria - Bala, Ezekiel Clement; Mohammed, Murtala; Afolabi, Nathanael (Kashere Journal of Politics and International Relations, 2025)
This paper seeks to find the relationship between the educational attainment of the head of household and living standard of the poor and vulnerable households in Nigeria. Nigeria as a country has been plagued with a high rate of poverty. With an estimated population of over 200 million people, Nigeria is Africa's most populous nation and the largest economy in Sub-Saharan Africa; however Poverty remains at 40.1 per cent in 2018/19, and is set to rise to about 42.6 per cent in 2022 implying a lower living standard for many of the populace. On the other hand, it is widely accepted that those with higher incomes tend to have better health, more education and a greater ability to participate in the social and political lives of their communities therefore having a better living standard. This study examined the relationship between the educational attainment of the head of household on the living standard of the household in Nigeria using the spearman’s correlation coefficient and secondary data from the National Social Register collected by the National Social Safety Nets Coordinating Office. The results obtained reveal that there is a strong tendency for lower educational attainment to be associated with a higher prevalence of household poverty or lower living standards. Literacy of the household head is also inversely related to household poverty